Divorce, Annulments, and the Catholic Church - Everett, Craig, author.
1 online resource (266 pages)
Keywords: Explore the meaning of annulment to Catholics and the Church!This valuable book examines the use of annulment by the Catholic Church to grant divorced Catholics the right to remarry within the Church. Divorce, Annulments, and the Catholic Church: Healing or Hurtful? is the first published study on annulments with wide-scale usage of questionnaires and interviews comparing Catholics who have sought an annulment with divorced Catholics who have not sought an annulment as well as married Catholics. In addition to delivering a quantitative analysis of the responses to various questions (religious, social, or psychological), it explains in lay terms what annulments are and what the acceptable grounds are for annulment and takes you step-by-step through the process of obtaining one. This insightful book also contains case studies of individuals who have been hurt by annulments and offers suggestions on how people who want to contest an annulment should proceed.This well-referenced book: explores the factors that lead to divorce provides a theoretical perspective as to why people either support or oppose annulments examines the religious influence on divorce and remarriage discusses the social integration-related aspects of annulment and divorce for Catholics presents recommendations for petitioners, respondents, clerics, and the members of tribunals who act as advocates, defenders, and judgesDivorce, Annulments, and the Catholic Church is an invaluable reference work for counselors dealing with the issue of divorce for Catholics, non-Catholics whose former spouses are seeking annulments, divorced Catholics who are contemplating an annulment, members of the clergy, and members of marriage tribunals and Family Life groups.